2016
DOI: 10.9738/intsurg-d-15-00176.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Thyroidectomy Outcomes Based on Surgical Method: A Comparison of LigaSure Precise, Harmonic Focus, and Traditional Methods

Abstract: New surgical devices have been developed to improve haemostatic control and vascular closure in thyroid surgery. Here, we compare the efficacy and clinical outcomes of 3 surgical methods, Harmonic Focus, LigaSure Precise, and the traditional suture-ligation method, in patients undergoing total thyroidectomies. This retrospective study compared total thyroidectomies performed between July 2008 and August 2012. Thyroidectomies were performed in 243 patients using Harmonic Focus (n ¼ 81), LigaSure Precise (n ¼ 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Many researchers have reported results similar to our study. These studies demonstrated statistically significant (p<0.005) difference in intraoperative bleeding between LigaSure small jaw group and conventional technique group [17,19,22,24]. In our study there was only one case of postoperative hematoma formation in the conventional vascular ligation group (0.9%) while none of the patients in the LigaSure group developed hematoma formation (p>0.05).…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® supporting
confidence: 41%
See 2 more Smart Citations
“…Many researchers have reported results similar to our study. These studies demonstrated statistically significant (p<0.005) difference in intraoperative bleeding between LigaSure small jaw group and conventional technique group [17,19,22,24]. In our study there was only one case of postoperative hematoma formation in the conventional vascular ligation group (0.9%) while none of the patients in the LigaSure group developed hematoma formation (p>0.05).…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® supporting
confidence: 41%
“…In their comparative study Ciftci showed difference in operative times (∼15%) between harmonic and traditional suture tie groups but this difference was not statistically significant. The shorter operative times associated with Harmonic Focus are likely due to its unique ultrasound-based technology, which enables simultaneous cutting and coagulation [22]. A meta-analysis by Zhang et al also reported significant reduction in operative time in LigaSure group versus conventional suture ligation method (p<0.00001) [17,23].…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® mentioning
confidence: 99%
See 1 more Smart Citation
“…37 Ferri et al in their similar trial recorded the same findings, while Ciftici in their comparative study of using Liga Sure precise, focus harmonic, and conventional technique showed no differences in terms of postoperative complications among the three groups. 38,39 In the present study, the mean duration of hospital stay was shorter in Group A (1.98±0.18 days) than Group B (2.37±1.79 days); this difference was highly significant (p=0.001). The results are similar to results of the other researchers as Noori et al who reported that the mean hospital stay in his study was significantly shorter in harmonic scalpel group compared with conventional technique (20 h vs. 32 h).…”
Section: Discussionmentioning
confidence: 41%